Suitability of Hybrid Electric Powertrains with Electric Turbocharger - Arshad-Ali, Syed Kamran (My University, 2015)
This research investigates the effects of an electric turbocharger in a hybrid electric powertrain. First generic vehicle models are created and run to understand the overall powertrain requirements of torque, power and energy of a performance consumer vehicle. Then a low fidelity baseline model of a conventional vehicle is created in Simulink to serve as a baseline measure. To analyze an electric turbocharger system a high-fidelity model in AMESIM of a 4 cylinder turbocharged engine was modified. This engine model was analyzed using virtual dynamometer tests and a simplified look-up table based controller was developed for the electric motor within the electric turbocharger. Next this engine model was inserted within three different types of hybrid powertrain architectures models in AMESIM. Each hybrid powertrain required a unique supervisory controller which was developed using Stateflow in Simulink. These controller algorithms were imported into AMESIM and the model was simulated over standard drive cycles. Since a very wide variation of electrification level exists within hybrid powertrains the supervisory controllers are calibrated for charge-sustaining simulations. This allows for impartial comparisons across the hybrid architectures. Lastly a track drive cycle was developed to understand electric turbocharger effects under high performance loading conditions
Keywords: Hybrid; Electric Turbocharger; Powertrain